The impact of income on tax compliance: The empirical evidence from small and medium taxpayers of Sri Lanka - Nadee and Premaratna, D. (University of Jaffna, 2020)
Tax compliance has been examined from various perspectives by researchers since its impact on the economy is vital. This study aims to explore the relationship between the income and the taxpayer's compliance behavior using the assumptions in the Slippery-Slope Framework. The research focuses only on the small and medium level business community in Sri Lanka. The study empirically examines how a taxpayer's income influences tax compliance decisions with the perception of trust in the tax regime's authority and power. A self-administered questionnaire has been distributed to obtain the information needed from the target group and received 408 responses. Kendall's tau-b and Spearman's correlation coefficients were used to measuring the association's direction between two variables. The findings suggest that voluntary compliance has a positive connection, while enforced compliance shows a negative association with the taxpayer's income level. Also, the results prove that the level of income is a determinant of tax compliance. Besides, it has been established that the tax authority should take adequate measures to review the strategies developed to implement tax policy. This Research expects to give an insight into the operations of the revenue authority and decisions taken by policymakers and academics to explore the factors that encourage tax compliance.
Keywords: income level; slippery-slope framework; tax compliance